Strategies for Implementing Multicultural Education and Local Wisdom in Indonesia’s Border Areas under Globalization: A Socio-Cultural Learning Perspective (Systematic Literature Review) - Ramadhan, Iwan; Barella, Yusawinur; Yuniarti, Yuniarti; Yani T, Ahmad; Sulistyarini, Sulistyarini (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This article examines the impact of globalization on multicultural education and local wisdom in the border areas of Kalimantan. Globalization has brought significant changes to cultural values, potentially eroding local cultural identities, particularly among younger generations. Using a Systematic Literature Review (SLR) approach, this study systematically collected and analyzed 85 journal articles published between 2015 and 2024 from databases such as Google Scholar and Crossref, using keywords related to globalization, multicultural education, local wisdom, socio-cultural learning, and border areas. Data were analyzed through thematic synthesis to identify recurring patterns and conceptual linkages. The findings reveal that multicultural education serves as a strategic approach to preserving cultural identity and fostering inclusive, tolerant student character. At the same time, local wisdom reinforces the internalization of noble values—such as gotong royong (cooperation), respect, and patriotism. Furthermore, effective implementation requires synergy between educational institutions, local governments, and communities through inclusive curriculum development, teacher capacity building, and community-based learning initiatives. In conclusion, this study makes a significant contribution both theoretically and practically by proposing a conceptual model and implementing strategies for integrating socio-cultural learning into multicultural education. It highlights the importance of strengthening cultural resilience in border regions through sustainable, context-based educational transformation in response to globalization.